HAK WARIS BAGI PEMOHON EUTHANASIA PERSPEKTIF HUKUM ISLAM - Rouf, Abd. (Fakultas Syariah, 2012)
This study aims at answering the problem of inheritance rights for the euthanasia applicant. In its legal istinbÃ¢th, researcher used killing act law that contains in hadith Ø¨Ø±Ù‚Ø£ Ù‡Ø«Ø±Ø§ÙˆÙ Ø«Ø±Ø§Ùˆ Ù‡Ù„ Ù†ÙƒÙŠ Ù…Ù„ Ù†Ø¥Ùˆ Ø¡ÙŠØ´ Ù„ØªØ§Ù‚Ù„Ù„ Ø³ÙŠÙ„ Ø§Ø¦ÙŠØ´ Ù„ØªØ§Ù‚Ù„Ø§ Ø«Ø±ÙŠ Ù„Ùˆ Ù‡ÙŠÙ„Ø¥ Ø³Ø§Ù†Ù„Ø§ as Al-Aslu by deciding Illat within the hadith that is killing (killing motive). The original law contained in the Hadith is unlawful for the murderer to inherit from the person who has been killed and its al-far'u is passive euthanasia. From the result of this research, it is concluded that the legal status of the applicant's rights to inheritance for passive euthanasia, it is hindered for the applicant to inherit property from the heir to the respondent. Â Penelitian ini adalah untuk menjawab permasalahan hak waris bagi pemohon euthanasia.. Dalam istinbÃ¢th hukumnya, peneliti menggunakan hukum tindakan pembunuhan yang terdapat dalam hadits Ø§Ø¦ÙŠØ´ Ù„ØªØ§Ù‚Ù„Ø§ Ø«Ø±ÙŠ Ù„Ùˆ Ù‡ÙŠÙ„Ø¥ Ø³Ø§Ù†Ù„Ø§ Ø¨Ø±Ù‚Ø£ Ù‡Ø«Ø±Ø§ÙˆÙ Ø«Ø±Ø§Ùˆ Ù‡Ù„ Ù†ÙƒÙŠ Ù…Ù„ Ù†Ø¥Ùˆ Ø¡ÙŠØ´ Ù„ØªØ§Ù‚Ù„Ù„ Ø³ÙŠÙ„ sebagai al-Ashlu dengan menetapkan â€˜illat yang terkandung di dalamnya yaitu menghilangkan nyawa (adanya motif pembunuhan). Adapun hukum asal yang terdapat dalam hadits tersebut adalah haram hukumnya bagi pembunuh mewarisi dari orang yang dibunuhnya dan al-farâ€™u adalah euthanasia pasif. Dari hasil penelitian tersebut, maka diperoleh kesimpulan bahwa status hukum hak waris bagi pemohon euthanasia pasif adalah pemohon euthanasia terhalangi haknya untuk mewarisi harta dari pewaris yang menjadi termohon. Â Â